Foto Produk UKM (Usaha Kecil Dan Menengah) Di Pasar Johar Selatan Kota Semarang - Althof Nafis Zahran; Geget Praditia Aji; Farrel Jeremy Hasyim; Alifina Khowash; Dwi Pujiono (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
In this digital era, product photos play a crucial role as the main tool to attract the attention of potential consumers. Community service in the form of product photography services emerged as a promising solution. This product photography service not only provides access to good quality product photos, but can also empower small and medium businesses to increase their presence in an increasingly competitive online market. This Community Service focuses on providing product photography services for Small and Medium Enterprises (UKM) located on the 3rd and 4th floors of South Johar Market, Semarang City. This service aims to provide photo services for products owned by various SMEs in Johar Market, such as food, handicrafts, shoes, batik cloth, etc. The results of this service include journal publications, training modules, documentation, press releases and final reports. It is hoped that this service can make a real contribution in strengthening the local business ecosystem and encouraging economic inclusion for all parties involved.